Endovascular treatment with versus without tirofiban for stroke patients with large vessel occlusion: The multicenter, randomized, placebo-controlled, double-blind RESCUE BT study protocol. Issue 10 (December 2022) - Qiu, Zhongming; Li, Fengli; Sang, Hongfei; Liu, Wenhua; Huang, Wenguo; Li, Huagang; Zhang, Min; Zhou, Peiyang; Lei, Bo; Zhou, Zhiming; Saver, Jeffrey L; Nogueira, Raul G; et al.
Background: Tirofiban, a glycoprotein IIb/IIIa receptor inhibitor, has been shown to reduce the risk of thrombotic complications during percutaneous coronary intervention. However, it remains unknown whether tirofiban improves outcomes in large vessel occlusion stroke patients undergoing endovascular treatment. Objective: This trial aims to assess whether additional intravenous tirofiban therapy can improve the clinical outcomes in large vessel occlusion stroke patients who undergo endovascular treatment within 24 h of symptom onset. Methods and design: The Endovascular Treatment With versus Without Tirofiban for Stroke Patients With Large Vessel Occlusion (RESCUE BT) Trial is an investigator-initiated, randomized, placebo-controlled, double-blind, multicenter trial. Up to 930 eligible patients will be consecutively randomized to intravenous tirofiban or placebo in 1:1 ratio over 3 years across 50 endovascular-capable stroke centers in China. Outcomes: The primary end point is the disability level as measured by overall distribution of the 90-day modified Rankin Scale scores. Primary safety end points include symptomatic intracerebral hemorrhage at 48 h and mortality at 90 days. Trial registry number: ChiCTR-INR-17014167 (www.chictr.org.cn ).